2017
DOI: 10.1016/j.anpedi.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

En Cataluña la enfermedad de Kawasaki es más prevalente en las zonas rurales

Abstract: This is the first population-based study showing significant differences on KD incidence rates between rural and non-rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
2
0
3
Order By: Relevance
“…Similar to US studies, migration studies performed in the United Kingdom and Spain showed a higher incidence for children with an Asian origin than white peers ( 22 , 24 , 31 ). In England, a significant association was found between Chinese ethnicity and incidence of KD, peaking at 13.6 instead of 6.6 in areas with more than 1% of the population of Chinese ethnicity as compared with areas with low (<0.18) population of Chinese ethnicity ( 24 ).…”
Section: Ethnicity and Migration Studiessupporting
confidence: 70%
See 2 more Smart Citations
“…Similar to US studies, migration studies performed in the United Kingdom and Spain showed a higher incidence for children with an Asian origin than white peers ( 22 , 24 , 31 ). In England, a significant association was found between Chinese ethnicity and incidence of KD, peaking at 13.6 instead of 6.6 in areas with more than 1% of the population of Chinese ethnicity as compared with areas with low (<0.18) population of Chinese ethnicity ( 24 ).…”
Section: Ethnicity and Migration Studiessupporting
confidence: 70%
“…However, no children were Chinese, Japanese, or from other countries in the east of the Indian subcontinent but rather were of Indian, Pakistani, or Bangladeshi origin. In Spain, KD was more common in Asian and North African children ( 31 ).…”
Section: Ethnicity and Migration Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…La etiología de la EK todavía se desconoce, aunque sus características clínicas, analíticas y epidemiológicas sugieren un origen o desencadenante infeccioso 3 . De igual forma, es bien conocido el hecho de que la EK es la causa más común de enfermedad cardíaca adquirida, que por lo general se desarrolla antes de los cinco años de edad 1 .…”
Section: Introductionunclassified
“…La etiología de la EK todavía se desconoce, aunque se piensa en un origen o desencadenante infeccioso 3,6 , y es que incluso, en las hipótesis con Conclusión: la enfermedad de Kawasaki y el síndrome inflamatorio multisistémico poseen similitud en cuanto a manifestaciones clínicas se refiere, así como también, de acuerdo a las hipótesis, podrían estar explicadas por una infección viral como desencadenante de la enfermedad; ambas presentan afectación a nivel ocular, gastrointestinal y cardíaca.…”
Section: Introductionunclassified